Enhancing Urban Livability Place Making of Outdoor Spaces within Transit-Oriented Development (TOD): A Study Case on Rajawali Station, Jakarta - Abednego, Ivan Adiel; Ronaldo, Christopher (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2024)
Urbanization profoundly impacts urban spaces, often resulting in inadequate planning, integration, and sustainability. Enhancing urban livability can overcome these problems with Place Making of Outdoor Spaces within Transit-Oriented Development (TOD). This study integrates insights from two research perspectives: firstly, exploring sustainability in outdoor spaces broadly through behavior mapping, documentation, and semi-structured interviews; secondly, focusing specifically on Rajawali Station in Jakarta. Despite Jakarta’s TOD emphasis, gaps persist in implementing placemaking principles effectively. Employing qualitative methods, including behavior mapping and stakeholder interviews, this research assesses current usage patterns and proposes placemaking strategies for Rajawali Station. Based on the identification results, a mechanism for using outdoor space is needed to improve the quality of urban livability. Apart from that, based on the evaluation results, collaboration is needed in the use of outdoor space by users. The impact of this collaboration can produce design recommendations based on sustainable human orientation. These recommendations are crucial for guiding sustainable urban development efforts and fostering community-centric outdoor spaces within TODs.